Reputasi institusi dan ketersediaan informasi dalam mempengaruhi kepercayaan dan dampaknya pada niat menjadi mahasiswa - Hartono, Bambang Sri; Rosia, Rina (Nur Science Institute, 2021)
The reputation of a college can cause many students who want to register and study at the college. Therefore, there is a very good impact related to many students, the first is income, and the second is academic and student activities. The purpose of this study was to examine and analyze the effect of institutional reputation and the availability of information on trust. Besides that, to analyze the effect of trust on the intention to be a student. This research was conducted on students of the Faculty of Economics, and Islamic Business IAIN Salatiga accepted and re-registered. The sample in this study was 151 students using the purposive sampling method. The results showed that the availability of information did not affect trust. However, the institution's reputation had a positive effect on trust, and trust had a significant effect on the intention to be a student of the Islamic Economics and Business Faculty IAIN Salatiga.